Work from home: a boon in the phase of pandemic? (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In this phase of pandemic and lockdown, where people are trying to cope up with stress along with their personal and professional responsibilities; do work from home acts as a boon to them? Flexible working arrangement enables the employees to avoid daily commutes and work according to their convenience but in this pandemic situation where people are bound to isolate themselves with their family, is flexible working helping them?Previously, there was a mindset that an efficient workforce can be developed through a proper work environment and team work but after this pandemic, a new mode of working has replaced the traditional one. At present, ‘work smart’ has replaced ‘work hard’ by accepting and incorporating employees’ multiple demands related to work and health, family and responsibilities , time and place. Work from home is one of the Flexible working arrangements provided by the employers to employees; also emerged as the “new normal strategy” after this pandemic. The IOT (Internet of Things) became essential for organizations to pace up the work. However, with digital platforms and up gradation of technology, the firms and organizations stay connected with their employees. This study is descriptive in nature and it focuses on both the pros and cons of flexible working along with its effect on the employees’ well-being and overall organizational work culture and productivity.